Oxytocin Rapidly Changes Astrocytic GFAP Plasticity by Differentially Modulating the Expressions of pERK 1/2 and Protein Kinase A - Wang, Ping; Qin, Danian; Wang, Yu-Feng (Frontiers in Molecular Neuroscience, 2017)
The importance of astrocytes to normal brain functions and neurological diseases has been extensively recognized; however, cellular mechanisms underlying functional and structural plasticity of astrocytes remain poorly understood. Oxytocin (OT) is a neuropeptide that can rapidly change astrocytic plasticity in association with lactation, as indicated in the expression of glial fibrillary acidic protein (GFAP) in the supraoptic nucleus (SON). Here, we used OT-evoked changes in GFAP expression in astrocytes of male rat SON as a model to explore the cellular mechanisms underlying GFAP plasticity. The results showed that OT significantly reduced the expression of GFAP filaments and proteins in SON astrocytes in brain slices. In lysates of the SON, OT receptors (OTRs) was co-immunoprecipitated with GFAP; vasopressin, a neuropeptide structurally similar to OT, did not significantly change GFAP protein level; OT-evoked depolarization of astrocyte membrane potential was sensitive to a selective OTR antagonist (OTRA) but not to tetanus toxin, a blocker of synaptic transmission. The effects of OT on GFAP expression and on astrocyte uptake of Bauer-Peptide, an astrocyte-specific dye, were mimicked by isoproterenol (β-adrenoceptor agonist), U0126 or PD98059, inhibitors of extracellular signal-regulated protein kinase (ERK) 1/2 kinase, and blocked by the OTRA or KT5720, a protein kinase A (PKA) inhibitor. Finally, suckling increased astrocytic expression of the catalytic subunit of PKA (cPKA) at astrocytic processes while increasing the molecular associations of GFAP with cPKA and pERK 1/2. Upon the occurrence of the milk-ejection reflex, spatial co-localization of the cPKA with GFAP filaments further increased, which was accompanied with increased molecular association of GFAP with pERK 1/2 but not with cPKA. Thus, OT-elicited GFAP plasticity is achieved by sequential activation of ERK 1/2 and PKA via OTR signaling pathway in an antagonistic but coordinated manner.